2015
DOI: 10.6023/cjoc201411030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anion Recognition of Acyclic Ferrocene-Based Imidazole Receptors

Abstract: The design and synthesis of artificial receptors capable of binding and sensing anions have been widely explored in the field of host-guest chemistry. Herein, a series of acyclic ferrocene-based imidazolium receptors 3a~3e were designed and synthesized. All the receptors were prepared by reactions of 1-(ferrocenylmethylene)imidazole 1 with corresponding dibromides in solvent under refluxing, followed by anion exchanges with NH 4 PF 6 . The structures of all the products were determined by IR, 1 H NMR, 13 C NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…All 1,1′‐bis(1‐ferrocenylmethyl)‐3,3′‐alkylenediimidazolium bromides were synthesized using the synthetic procedure described in the literatures. [10a], [10b] Potassium 1,1,3,3‐tetracyanopropenide, pyridinium 1,1,2,3,3‐pentacyanopropenide, and tetraethyl ammonium 1,1,2,5,6,6‐hexacyano‐3,4‐ diazahexadienediide were synthesized as described by W. J. Middleton . [10c] 1 H and 13 C NMR spectra were performed with a Bruker Avance 400 MHz spectrometer unless indicated otherwise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 1,1′‐bis(1‐ferrocenylmethyl)‐3,3′‐alkylenediimidazolium bromides were synthesized using the synthetic procedure described in the literatures. [10a], [10b] Potassium 1,1,3,3‐tetracyanopropenide, pyridinium 1,1,2,3,3‐pentacyanopropenide, and tetraethyl ammonium 1,1,2,5,6,6‐hexacyano‐3,4‐ diazahexadienediide were synthesized as described by W. J. Middleton . [10c] 1 H and 13 C NMR spectra were performed with a Bruker Avance 400 MHz spectrometer unless indicated otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…[10a], [10b] Potassium 1,1,3,3‐tetracyanopropenide, pyridinium 1,1,2,3,3‐pentacyanopropenide, and tetraethyl ammonium 1,1,2,5,6,6‐hexacyano‐3,4‐ diazahexadienediide were synthesized as described by W. J. Middleton . [10c] 1 H and 13 C NMR spectra were performed with a Bruker Avance 400 MHz spectrometer unless indicated otherwise. Elemental analyses were carried out with a Vario EL III Elemental Analyzer, Germany.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, a series of acyclic and trinuclear ferrocene-based imidazolium receptors noticeably improved selectivity toward the F À anion. [8][9][10] Structural characterization of other ferrocenyl imidazole derivatives showed that specic recognition properties involve the ferrocene being linked directly with the C2 of imidazole, with the C4 and C5 fused to a conjugative system. One of the receptors discovered was 2-ferrocenyl-1H-anthra [1,2-d]imidazole-6,11(5aH,11aH)-dione, which was capable of detecting [CN À ] aq as low as $0.1 ppm.…”
Section: Introductionmentioning
confidence: 99%